Meta-Analysis the Efficacy of Turmeric (Curcuma domestica) in Reducing Pain in Patients of Knee Osteoarthritis - Ardiyanto, Danang; Tamtomo, Didik Gunawan; Murti, Bhisma (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Osteoarthritis (OA) of the knee joint has the highest prevalence among all types of rheumatic diseases. The most common symptom of knee OA is pain around the joint. Patients with OA require long treatment, especially using analgesic and anti-inflammatory drugs. Turmeric is efficacious as a pain reliever and anti-inflammatory. This study aims to estimate the magnitude of the effect of turmeric extract (Curcuma domestica) on pain in patients with knee OA compared to placebo and non-steroidal anti-inflammatory drugs (NSAIDs), based on the results of a number of previous similar studies.Subjects and Method: This study is a systematic review and meta-analysis with the following PICO, population: patients with knee OA. Intervention: turmeric extract. Comparison: placebo and NSAIDs. Outcome: pain reduction. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. Keywords to search for articles: “Knee Osteoarthritis” OR “Knee OA” AND “Curcuma longa” OR “Curcuma domestica” OR “Turmeric extract” AND “Placebo” OR “NSAID” AND “pain” OR “visual analogue scale” OR “ VASE